Designing of smart shoe. (2020) - Manjunathan, A.; Bhuvaneshwari, C.
Abstract: In this research work, to helps the blind peoples to sense the obstacles and to navigate from one place to other freely. Shoe is designed for general navigation purpose, in which to implementing a transmitter and receiver to detect the object. The sensor head emanates an ultrasonic wave and gets the wave reflected back from the target. Using PIC for transmitting signal to vibrator, in which PIC acts as a microcontroller and vibration is vary from 1 to 3 m. The red light is just to show that the blind people are in the side of the road.